PERBEDAAN METODE PEMBELAJARAN BERBASIS LINGKUNGAN TERHADAP HASIL BELAJAR GEOGRAFI DAN KEMAMPUAN BERIKIR KRITIS SISWA KELAS X SMA NEGERI 3 JAYAPURA - Tanawani, Karolina (Magister Pendidikan IPA, UNCEN, 2014)
Abstract. The purpose of this study was to examine differences in method-based learning environments on learning outcomes and critical thinking skills of students on the subject of soil erosion. The design of this study used a Control Group Design Pettern Pre Test â Post Test (The Pre Test â Post Test Control Group Design). The conclusion o this study, that the application of the environment-based learning method in the delivery of the subject is very appropriate soil erosion Therefore the application of environment-based learning method can be applied in any nuanced spatial geography teaching materials. Keywords: Environment-based learning method, the conventional method, learning outcomes and studentsâ critical thinking skills.